Standardization in the Accounting of Public Sector Enterprises - Feschian, Daniela; Pavlova, Veselka (Research Papers, 2014)
This paper analyzes the major problems in the accounting of the public sector enterprises created by the lack of standardization. It aims to prove the need to introduce standardization and develop an accounting model based on the International Accounting Standards in the public sector. Two major trends are examined:Deviations from the fundamental accounting practices in the reporting of specific objects in public sector enterprises are exposed and proposals are made with regard to their elimination. Furthermore, the possible effects that the proposed standardized models may have on reporting are suggested.This paper also presents an analysis of the findings of a specialized survey on the problems of accounting system of public sector enterprises, and in the state universities in particular. This research validates the hypothesis that the public sector enterprises lack a standardization of their accounting systems. As a result it establishes deviations from leading principles such as the current charging, the comparability of revenues and expenditures, caution and others. This research also proves the need to standardize the accounting system of public sector enterprises whereby a significant part of the problems will be removed and the quality of accounting information will be considerably improved.